Interleukin-8 in Hyperlipidemia and Coronary Heart Disease in Thai Patients Taking Statin Cholesterol-Lowering Medication while Undergoing Coronary Artery Bypass Grafting Treatment - Wilanee Dechkhajorn (2020)
© 2020 Wilanee Dechkhajorn et al. The role of interleukin-8 (IL-8), a pivotal chemokine in atherogenesis and coronary heart disease (CHD) development, is diverse and remains unclear. This cross-sectional study investigates the association of the IL-8 expression in hyperlipidemia (H) and CHD patients who have been treated with statin cholesterol-lowering drugs while undergoing coronary artery bypass grafting treatment. Fifty-five Thai volunteers including 13 normal (N), 24 H, and 18 CHD patients were enrolled for the investigation. All the CHD patients had been treated continuously with statin cholesterol-lowering medications since the disease was diagnosed and were undergoing coronary bypass grafting approximately one month later. Therefore, the CHD group was representative of a pathogenesis improvement in CHD. The IL8 mRNA expression was determined by real-time quantitative PCR in the peripheral blood mononuclear cells from heparinized blood. The plasma IL-8 levels were assessed by enzyme-linked immunosorbent assay. The result shows that the IL8 mRNA expression in the H group tended to increase; however, in the CHD group, there was a significant decrease (p=0.0111) compared to the N group. The IL8 mRNA expression and the plasma levels in the CHD group were significantly lower than those in the H group (p<0.05). A significant negative correlation between the IL8 mRNA (r = -0.499) or plasma IL-8 (r = -0.3875) expression and CHD progression was observed (p<0.05). In conclusion, the transcriptomic and the phenotypic IL-8 expression decreased significantly in the Thai CHD patients who had continuously received statin-group medications compared to the H and N group participants. Therefore, IL-8 should serve as a feasible marker and could be used to evaluate the therapeutic effects of statins and illustrate the pathology of CHD treatment.